Fusion, direct and total reaction cross sections of the Â¹Â°B+Â¹â ´N system up to E/sub 14N/ = 180 MeV - Ortiz, M. E.; Gomez del Campo, J.; Chan, Y. D.; Di Gregorio, D. E.; Ford, J. L. C.; Shapira, D. (American Institute of Physics, 1982)
Fil: Di Gregorio, D. E. Comisión Nacional de Energía Atómica; Argentina